Friction properties of the face of a hand-held tennis racket - Maeda, H.; Okauchi, M. (Procedia Engineering, 2012)
The feel of hitting a tennis ball with topspin is related to the friction force of the plane of the racket face, and it is also related to the vibration of the racket. In order to measure the friction and the vibration, we attached gauges to the strings and the throat of two brands of tennis racket. At incident angles under 30 degrees, the ball was observed to slip on the racket face. At angles over 45°, the action duration of friction was almost as long as the vibration period of the racket shaft. From this result, we predict that the feel of hitting is related to the stiffness of the racket shaft.